AB0359 Clinic profile of patients with rheumatoid arthritis and pulmonary affection in a cohort from a university hospital. (12th June 2018) - Casafont Solé, I.; Prior-Español, Á.; Holgado, S.; Roca, J.; Mateo, L.; García-Mira, Y.; Camins, J.; Gifre, L.; Riveros, A.; Martínez-Morillo, M.; Aparicio, M.; Olivé, A.
Abstract : Background: Pulmonary affection is a serious complication in Rheumatoid Arthritis (RA) with an important impact on mortality and morbidity. Objectives: To describe the clinical and radiographic characteristics of patients with RA in our centre, and specifically from those with interstitial lung disease (ILD). Methods: Retrospective analysis of patients with RA and pulmonary affection from a University Hospital with a referral area of 85.000 inhabitants. Clinical, laboratory, imaging and pulmonary function test (PFT) data was recorded. Results: Data from 85 patients, 37 (43.5%) male and 48 (56.5%) female, were recorded. The mean time from RA diagnosis to pulmonary disease was 9.2 years, with mainly erosive (58.8%) and seropostive (84.7% were positive rheumatoid factor (RF) and 84.2% anti-citrullinated protein antibodies (ACPA)) disease. The 56.5% of the patients were smokers or ex-smokers. PFT results were documented in 75.3% of the patients: diffusing capacity for carbon monoxide (DCLO) baseline values were over 60% in a 38.8% of cases and forced vital capacity (FVC) baseline values were over 50% in a 69.4% of patients. The most frequent High Resolution CT scan pattern was the presence of bronchiectasis (64.7%), followed by ILD (31.8%) and, specifically, the Usual Interstitial Pneumonia pattern (UIP, 66.6%); lung infections (25.8%), rheumatoid lung nodules (22.4%), pleural effusion (15.3%), lung tumours (9.4%) and bronchiolitis (5.8%). The presence of extra articular manifestations as rheumatoid nodules (27%), epieschleritis (2.3%) and vasculitis (9.4%) was registered. The coexistence of Chronic Obstructive Pulmonary Disease (COPD) was recorded too (24.7%). Related to treatment, 84.7% of patients had received Methotrexate and in a 40% of cases, at least one biological disease-modifying antirheumatic drug had been administrated. Though the causes were not registered, a 25.9% of deaths were documented. In parallel we did a subanalysis of ILD related to RA cases, summarised in table 1 (n=27): Conclusions: Bronchiectasis is the most common pulmonary manifestation of RA patients in our area. The most frequent clinical profile is a non-smoker woman with seropositive disease. ILD affects approximately one third of RA patients in our area and is an underdiagnosed entity. We consider that it is necessary to establish a screening program to diagnose and treat it early. Disclosure of Interest: None declared